Awareness, knowledge, and psycho-emotional aspect of infertility among women seeking fertility assistance at a tertiary care hospital in Chhattisgarh, a cross-sectional study - Vinita Singh; Gitika Rajpal; Sagarika Majumdar; Sucharita Mandal; Rajshree Sahu (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The lack of fundamental knowledge and awareness about the biological process of reproduction is low worldwide but has reportedly higher incidence rates in under-developed countries. Infertility can have a tremendous effect on a woman's psychological and social well-being, pushing her toward mental stress, anxiety, depression self-blame, self-isolation, feeling of worthlessness, and lack of interest in life. The present study was conducted to determine the level of knowledge and awareness regarding factors affecting fertility and also to ascertain the emotional status of females visiting the Obstetrics and Gynecology out-patient department for fertility assistance. MATERIALS AND METHODS: A cross-sectional study was performed by using a questionnaire which had two parts; the first part had questions about awareness and knowledge of the subject of infertility, and the second part had 12 questions that assessed the psychological and emotional status of the participants, and it also explored prevailing myths about infertility based on a validated questionnaire. RESULTS: There was a significant difference in mean knowledge score; those who were more educated had better knowledge of various aspects of infertility. The overall adequacy for knowledge and awareness revealed that only 62 (47.7%) of the participants had adequate knowledge (score >6) regarding female infertility. The mean score for knowledge among all the respondents was 6.61 ± 1.48. The overall emotional and psychological score suggested that 30 (23%) of the respondents were disturbed because of stress because of infertility. CONCLUSION: Infertility can have a serious impact on the psychological well-being of females, and social pressure and stigma associated with childlessness can further worsen the physical and emotional well-being of couples, which needs to be addressed before starting treatment of infertility for a better response to treatment. The limited knowledge and prevailing mis-conceptions regarding infertility need to be sincerely dealt with to complement the medical treatment of infertility.